On 3D-printed ZnO-reinforced PLA matrix composite: Tensile, thermal, morphological and shape memory characteristics. (October 2022) - Singh, Mohit; Singh, Rupinder; Kumar, Ranvijay; Kumar, Pawan; Preet, Pawan
The zinc oxide (ZnO)-reinforced polylactic acid (PLA) matrix has established shape memory characteristics. But hitherto little has been reported on two-way programmed 3D-printed ZnO-reinforced PLA functional prototypes (prepared on commercial fused deposition modelling (FDM) set-up). This article reports the effect of 3D printing process parameters on tensile, thermal, morphological and two-way programmed shape memory characteristics of ZnO-reinforced PLA-based functional prototypes. It has been ascertained that the maximum strength at peak (14.32 MPa) and maximum strength at break (12.89 MPa) were observed for sample printed at 80% infill density, four number of perimeters with triangular pattern. Maximum Young's modulus (233.68 MPa) was observed for samples printed at 80% infill density and three perimeters with honeycomb pattern. Also, the maximum modulus of toughness (0.883 MPa) was observed in case of sample printed at 80% infill density, five perimeters with rectilinear pattern. Further based upon thermal analysis using differential scanning calorimetry, it has been ascertained that there is no significant effect of FDM process parameters on normalized heat capacity of functional prototype. As regards to two-way programmed specimens, it has been observed that the porosity of functional prototypes increase with 30 min immersion in water as stimulus at 70°C and it again decreases (regain) after 30 min exposure at atmospheric temperature. Contrary to this, the samples' porosity values decrease with 30 min immersion in water at 10 ° C and regain after 30 min exposure at atmospheric temperature. Further some effect of shape memory has been noticed on functional prototypes volume and weight at two different temperatures.